An Investigation on the Detection and Distribution of Biofilm Production Caused Uropathogenic Escherichia coli in Tropical Catheterized Patients by Tube Adherence Method - Bhardwaj, Ashwani (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Infections of the urinary tract, commonly known as urinary tract infection (UTI), are very common and prevalent issue among patients in the general outdoor clinics. Moreover, association of biofilms further raises concerns in terms of the recurrence of UTI or resistance microorganisms. Objective: The objective of the present study includes the investigation of the distribution and detection of biofilm production by uropathogens in tropical catheterized patients by the tube adherence method (TAM). Materials and Methods: A total of 100 patients were included in the study. All the patients were tropical catheterized patients admitted in Civil Hospital, Ambala City. The patients were consulted, and the required necessary medical information was recorded in a pre-defined format for easy retrieval. Urine samples were collected and microorganisms identified alongside detected the biofilm production in the samples. Results and Discussion: The results demonstrated the prevalence of UTIs among the study patients and Escherichia coli had been detected as the most predominant uropathogen responsible for the infection in the catheterized patient. Another hallmark observation demonstrated that resistant E. coli cases were most abundant among the isolated and suggestive of strong producer of biofilm. The results also indicated that, as a cost-effective method, TAM is a reliable method for biofilm detection in the present studied patient population. Conclusion: This method had been demonstrated to most accurate when the causative organism is resistant E. coli.